Bygones Worth Remembering, Vol. 2 (of 2) - Holyoake, George Jacob, 1817-1906 (Salt Lake City, UT : Project Gutenberg, 2011)
"Bygones Worth Remembering, Vol. 2 (of 2)" by George Jacob Holyoake is a collection of historical accounts and reflections, likely written in the late 19th century. This work delves into the lives and thoughts of prominent figures of the time, such as Mr. Gladstone and Herbert Spencer, exploring their contributions to society and the complexities of their characters. Through his narratives, Holyoake presents a candid and insightful examination of political and philosophical developments in his era." "The opening of the book highlights Holyoake's engaging conversations with historical giants like Mr. Gladstone, capturing the essence of their personalities and ideologies. It paints a vivid picture of a breakfast gathering with Gladstone, where lively discussions and anecdotes unfold, showcasing Gladstone's wit and breadth of knowledge. Holyoake reflects on the significance of these interactions, emphasizing the influence of these figures on contemporary thought and politics. This introduction effectively sets the stage for a deeper exploration of both the individuals discussed and the socio-political climate of the period, inviting readers to consider the lessons and legacies of the past." (This is an automatically generated summary.)
Conversations with Mr. Gladstone -- Herbert Spencer, the thinker -- Singular career of Mr. Disraeli -- Characteristics of Joseph Cowen -- The peril of scruples -- Taking sides -- Things which went as they would -- Story of the Lambeth palace grounds -- Social wonders across the water -- The Established Church at sea -- Adventures in the street -- Limping thrift -- Mistrust of moderation -- Penal Christianity -- Two Sundays -- Byways of liberty -- Lawyers' license -- Christian days -- New convictions which came unsought -- Diffuculty of knowing men -- Ideas for the young -- Experiences on the warpath -- Looking backwards.
Release date is 2011-07-20
Produced by David Widger
Keywords: Social reformers -- Great Britain -- Biography; Holyoake, George Jacob, 1817-1906; Working class -- Great Britain -- Biography